Maximizing Specific Loss Power for Magnetic Hyperthermia by Hard–Soft Mixed Ferrites. Issue 29 (21st June 2018) - He, Shuli; Zhang, Hongwang; Liu, Yihao; Sun, Fan; Yu, Xiang; Li, Xueyan; Zhang, Li; Wang, Lichen; Mao, Keya; Wang, Gangshi; Lin, Yunjuan; Han, Zhenchuan; et al.
Abstract: Maximized specific loss power and intrinsic loss power approaching theoretical limits for alternating‐current (AC) magnetic‐field heating of nanoparticles are reported. This is achieved by engineering the effective magnetic anisotropy barrier of nanoparticles via alloying of hard and soft ferrites. 22 nm Co0.03 Mn0.28 Fe2.7 O4 /SiO2 nanoparticles reach a specific loss power value of 3417 W g −1 metal at a field of 33 kA m −1 and 380 kHz. Biocompatible Zn0.3 Fe2.7 O4 /SiO2 nanoparticles achieve specific loss power of 500 W g −1 metal and intrinsic loss power of 26.8 nHm 2 kg −1 at field parameters of 7 kA m −1 and 380 kHz, below the clinical safety limit. Magnetic bone cement achieves heating adequate for bone tumor hyperthermia, incorporating an ultralow dosage of just 1 wt% of nanoparticles. In cellular hyperthermia experiments, these nanoparticles demonstrate high cell death rate at low field parameters. Zn0.3 Fe2.7 O4 /SiO2 nanoparticles show cell viabilities above 97% at concentrations up to 500 µg mL −1 within 48 h, suggesting toxicity lower than that of magnetite. Abstract : By engineering the magnetic anisotropy of nanoparticles via alloying of hard and soft ferrites, specific loss power and intrinsic loss power are maximized at alternating‐current field parameters below the clinical safety limit. These biocompatible nanoparticles yield high cell death rate in cellular hyperthermia. Bone cement incorporating the nanoparticles can be heated efficiently at ultralow dosage.